The Oxford handbook of early Christian ritual - Uro, Risto; Day, Juliette ca. 20./21. Jh.; DeMaris, Richard E. ca. 20./21. Jh.; Roitto, Rikard (Oxford handbooks online Religion, 2018)
Generations of New Testament and early Christian scholars have produced detailed analyses of the belief systems of nascent Christian communities, including their ideological and political dimensions, but have by and large ignored ritual as an important element of early Christian religion and as a factor contributing to the rise and the organization of the movement. In recent years, however, scholars of early Christianity have begun to use ritual as an analytical tool for describing and explaining Christian origins and the early history of the movement. Such a development has created a momentum towards producing a more comprehensive volume on the ritual world of early Christianity employing advances made in the field of Ritual Studies. The Handbook will give a manifold account of the ritual world of early Christianity from the beginning of the movement up to the fifth century.